GAMBLING GAMES AND THE EFFECTS AMONG MUSLIMS OF NASAWARA SOUTH, NASAWARA STATE, NIGERIA: AN ISLAMIC PERSPECTIVE - Sulaiman, Yahaya; Sulaiman, Abdullahi Adamu (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2023)
Gambling is a form of behaviour that has been identified to have serious consequences on gamblers spiritual, health, academic, social relation and has been reported to be related to some criminal related behaviour. Recently, there is a general upsurge of gambling houses globally and Nigeria in particular. Nasarawa South has its own fair share of the growth in this game of chance; incidentally Muslim youths are deeply involved in it despite the strict stand of Islamic tenet on it. Though, the situation may be partly attributed to the general unemployment situation in the country. The aim and objective of this research is to educate Muslims on the effects and Islamic teachings as it to gambling and other related games in order to eradicate or drastically reduce the practice of gambling among Muslims in Nasarawa South. The study adopts survey design, where interview method was employed in the collection of data for the paper. The researchers consulted library materials, and sampled opinions of Islamic scholars, Muslim leaders, through personal contact and observations on factors, problems, challenges, effects and solutions to the game of lottery activities in the study area. From the data collected and analyzed, it is clearly discovered that, there are so many problems and challenges encountering gambling players in the study areas where by most of the gambling players are addicted to it. It is concluded that gambling should be eradicated due to its effects on Muslim Ummah. The paper also gave some recommendations that, there should be policy by government for which heavy tax are imposed on gambling, betting and lottery houses in the study area in order to curtail the spread of the menace of gambling in the environment.